Comprehensive analysis of sesame LRR-RLKs: structure, evolution and dynamic expression profiles under Macrophomina phaseolina stress - Yan, Wenqing; Ni, Yunxia; Zhao, Hui; Liu, Xintao; Jia, Min; Zhao, Xinbei; Li, Yongdong; Miao, Hongmei; Liu, Hongyan; Zhang, Haiyang (Frontiers in Plant Science, 2024)
Leucine-rich repeat receptor-like kinases (LRR-RLKs) can participate in the regulation of plant growth and development, immunity and signal transduction. Sesamum indicum, one of the most important oil crops, has a significant role in promoting human health. In this study, 175 SiLRR-RLK genes were identified in S. indicum, and they were subdivided into 12 subfamilies by phylogenetic analysis. Gene duplication analysis showed that the expansion of the SiLRR-RLK family members in the sesame was mainly due to segmental duplication. Moreover, the gene expansion of subfamilies IV and III contributed to the perception of stimuli under M. phaseolina stress in the sesame. The collinearity analysis with other plant species revealed that the duplication of SiLRR-RLK genes occurred after the differentiation of dicotyledons and monocotyledons. The expression profile analysis and functional annotation of SiLRR-RLK genes indicated that they play a vital role in biotic stress. Furthermore, the protein−protein interaction and coexpression networks suggested that SiLRR-RLKs contributed to sesame resistance to Macrophomina phaseolina by acting alone or as a polymer with other SiLRR-RLKs. In conclusion, the comprehensive analysis of the SiLRR-RLK gene family provided a framework for further functional studies on SiLRR-RLK genes.